(untitled) (Fiep Bulletin - online, 2012)
The sport of sailing is characterized by the use of the driving force of the wind, resulting in the displacement of the vessel. Knowledge of the wind factor and its ability to produce thrust is the main content for learning the sport. The methods and materials developed and applied courses in sailing Brazilians do not demonstrate an effective treatment of this content. Historically, sailing schools were created by sportsmen and their methodologies are based on technical knowledge, thus, his teaching style relied on teaching methods that emphasize the mechanical movement and knowledge of the contents sealed. The physical education profession has been regulated in 1998 and set out the professional’s performance in this area, as a result, all activities of a physical action is linked to the physical education teacher. The sailing lessons fall within the scope of performance of physical education course and thus must rely on the performance of this professional. With a group of thirty children and a period of two months of field research, courses have been developed with the sailing performance of different actors: an inexperienced sailor in the act of teaching, a sailor with teaching experience in sailing school and with experience in teaching Physical Education and a sailor and experienced in sailing classes. Through the qualitative research case study, observation and evaluation of diagnostic and formative functions, we analyzed the data generated with the objective to determine the outcome of the following central problem: what is the difference between the methods of basic sailing courses taught by sportsmen and by physical education teacher, teaching in the treatment of the element of nature wind, for children aged seven to eleven years and what the most effective?